2006
DOI: 10.1055/s-2006-932661
|View full text |Cite
|
Sign up to set email alerts
|

Validierung der Deutschen Version (Kompetenznetz „Chronisch entzündliche Darmerkrankungen”) des Inflammatory Bowel Disease Questionnaire IBDQ-D

Abstract: The Inflammatory Bowel Disease Questionnaire (IBDQ) is the standard disease-specific instrument for assessment of health-related quality of life (HRQOL) in patients with inflammatory bowel diseases (IBD). A German translation has not been validated. 415 outpatient IBD-patients (Crohn's Disease n = 306, Ulcerative Colitis n = 109) completed the German version of the IBDQ (Competence network IBD, IBDQ-D), the Hospital Anxiety and Depression Scale German Version (HADS-D) and the Questions on Life Satisfaction FLZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The primary outcome total health-related quality of life at week 12 was assessed using the validated IBDQ German version. [ 18 , 19 ] The IBDQ consists of 32 items with four subscales: bowel (10 items; scale ranging from 10 to 70), systemic (five Items; scale ranging from 5 to 35), emotion (12 items; scale ranging from 12 to 84), and social (five items; scale ranging from 5 to 35), all of which were rated on a 7-point Likert scale (1 = worst rating, 7 = best rating). A total score was then calculated ranging from 32 to 224, with higher scores indicating better health and scores above 170 indicating no impairment to quality of life.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome total health-related quality of life at week 12 was assessed using the validated IBDQ German version. [ 18 , 19 ] The IBDQ consists of 32 items with four subscales: bowel (10 items; scale ranging from 10 to 70), systemic (five Items; scale ranging from 5 to 35), emotion (12 items; scale ranging from 12 to 84), and social (five items; scale ranging from 5 to 35), all of which were rated on a 7-point Likert scale (1 = worst rating, 7 = best rating). A total score was then calculated ranging from 32 to 224, with higher scores indicating better health and scores above 170 indicating no impairment to quality of life.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, a difference of 16 points in the IBDQ was identified as a clinically relevant difference [ 17 , 33 ]. To detect this difference using a two-sample t-test with a 5% significance level and 90% power, and assuming a standard deviation of 23.04 points (as reported for a previous sample [ 19 ]), 37 patients per group were needed. Accounting for a maximum dropout rate of 20%, at least 92 patients needed to be enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we did not use clinical parameters measured by physicians to assess disease activity or IBD-specific knowledge tests (e.g., CCKNOW [47] or KQ [48] ). The SF-12 questionnaire did not assess HRQoL specifically for IBD, although HRQoL measurement tools designed for IBD patients (e.g., IBDQ-D [49] ) might be more sensitive. This may explain our null results for HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…66 IBDQ was validated into different languages versions and have further proved its validity, internal consistency and reliability in several validation studies worldwide. 64,65,[67][68][69][70][71][72][73][74][75][76][77] As new therapies in gastroenterology are rapidly emerging, PROMs are increasingly used in clinical decision-making. There is a need to support and educate the gastroenterologist on how to assess these tools to encourage them to use them in clinical practice.…”
Section: Discussionmentioning
confidence: 99%